Memory before modernity : practices of memory in early modern Europe - Kuijpers, Erika, 1967-; Pollmann, Judith; Müller, Johannes (Johannes M.), 1980-; Steen, Jasper van der (Studies in medieval and Reformation traditions, 2013)
This volume examines the practice of memory in early modern Europe, showing that this was already a multimedia affair with many political uses, and affecting people at all levels of society; many pre-modern memory practices persist until today.